Ask Alice: an artificial retrieval of information agent - Valstar, Michel F.; Baur, Tobias; Cafaro, Angelo; Ghitulescu, Alexandru; Potard, Blaise; Wagner, Johannes; André, Elisabeth; Durieu, Laurent; Aylett, Matthew; Dermouche, Soumia; Pelachaud, Catherine; Coutinho, Eduardo; et al. (2016)
We present a demonstration of the ARIA framework, a modular approach for rapid development of virtual humans for information retrieval that have linguistic, emotional, and social skills and a strong personality. We demonstrate the framework’s capabilities in a scenario where ‘Alice in Wonderland’, a popular English literature book, is embodied by a virtual human representing Alice. The user can engage in an information exchange dialogue, where Alice acts as the expert on the book, and the user as an interested novice. Besides speech recognition, sophisticated audio-visual behaviour analysis is used to inform the core agent dialogue module about the user’s state and intentions, so that it can go beyond simple chat-bot dialogue. The behaviour generation module features a unique new capability of being able to deal gracefully with interruptions of the agent.